“Vous en avez d’autres comme celui-ci?” (“Do you have any more like this one?”): Teaching Françoise Sagan’s 1954 Novel Bonjour tristesse to 21st-century Students - Mariah E Devereux Herbeck (Studies in 20th & 21st Century Literature, 2026)
“Vous en avez d’autres comme celui-ci?”: Teaching Françoise Sagan’s 1954 Novel Bonjour tristesse to 21st-century Students Since COVID, Americans’ interest in literature has dropped precipitously: “The percent of U.S. adults who read novels or short stories declined at a 17% rate, from 45.2 percent in 2012 to 37.6 percent in 2022” (Publishers Weekly)[1]. Instructors of literature courses are aware of this trend that certainly predates the pandemic. The first-week icebreaker prompt “What is your favorite book?” increasingly elicits the (disheartening) response, “I don’t like reading.” Inspiring students to read literature in a second language is challenging, but convincing them that reading, in general, is a worthwhile habit is both daunting and imperative. For the last 20 years, I have concluded my “Introduction to French Literature'’ course with Françoise Sagan’s Bonjour tristesse about 17 year-old Cécile’s summer on the Côte d’Azur. Students read the novel after analyzing works by Molière, Claire de Duras, Maupassant and Baudelaire (among others). Colleagues may raise eyebrows at the inclusion of the novel that Sagan wrote when she was only 18 given that “because of its popularity and the author’s celebrity status and hedonistic image, [the novel] has never been given much serious analysis by literary critics” (Saur 198).[2] Notwithstanding, Sagan’s novel proves an ideal choice for its relevance (my students are often 18-22), brevity (152 pages) and because this so-called “beach read” is deceptively complex. In recent years, students have increasingly expressed how much they enjoy Sagan’s novel, going so far as to ask, “Vous en avez d’autres comme celui-ci?” (Do you have other ones like this?). How should increased student appreciation for non-canonical novels (recent or “old”) shape the future of teaching literature? In this article, I propose to provide French literature instructors both with justification for Sagan’s 1954 novel in their 21st-century curriculum as well as sample lesson ideas to facilitate discussion of key literary concepts, terms and important themes. Additionally, and perhaps most useful to literature instructors in general, I provide specific examples of student reaction to Bonjour tristesse and explore what evolving interest in the novel can tell us about the future of literary studies in the second language classroom. [1]https://www.publishersweekly.com/pw/newsbrief/index.html?record=4377#: :text=In%202022%2C%2053%25%20of%20U.S.,points%20lower%20than%20in%202012. [2] Saur P.S. “Cécile in Françoise Sagan’s BONJOUR TRISTESSE: A Female Version of Albert Camus’s STRANGER?” Explicator, vol. 74, no. 4, 2016, pp. 197–201, https://doi.org/10.1080/00144940.2016.1235539.
Keywords: Bonjour Tristesse; Françoise Sagan; French Literature